(untitled) (Annals of Medical Research, 2021)
Aim: Chest X-ray (CXR) is the first step imaging method for childhood pneumonia. However, radiation exposure is the main concern especially during follow-up due to increased risk for malignancies. Therefore, thorax ultrasound (TUS) has been used recently as a complementary method to assess lung diseases. We aim to show if TUS is a useful diagnostic tool in childhood pneumonia by comparing CXR findings.Material and Methods: One hundred and twenty-four patients who presented with pneumonia (67 girls, 57 boys; mean age: 6.29±3.66 years) were prospectively included in our study. After the chest X-ray was performed for each patient, they underwent a TUS on the same day. Radiologists were blinded to any clinical data. Imaging findings were compared statistically.Results: Of 124 patients (67 girls, 57 boys; mean age: 6.29±3.66 years), 79 patients (63.7%) had bacterial and 39 patients (31.45%) had viral pneumonia. The overall sensitivity of TUS was 86.06% for detecting pneumonia. There was not any statistical difference between TUS and CXR for identifying pneumonia on the bacterial subgroup (p=0.157). TUS was more efficient in recognizing bacterial pneumonia rather than viral pneumonia (Z sensitivity = 5.33>1.96).Conclusion: The use of TUS for initial diagnosis and follow-up of childhood pneumonia should be considered as a complementary imaging method to CXR rather than a substitutive role. TUS is more useful in bacterial pneumonia rather than viral pneumonia by showing findings such as subpleural pneumonitis, consolidation, pleural and pericardial effusion, empyema and the response to the medical therapy.